Identification of Veillonella spp. on Tongue Plaque and Saliva Using Real-Time PCR - Karina Dhaniarti; Fathia Agzarine Deandra; Ariadna A Djais; Boy M Bachtiar (The Indonesian Journal of Dental Research, 2012)
Veillonella spp., Gram-negative obligate anaerobic cocci bacteria, amounts to 3% in the oral cavity, relies on the fermentation of lactate as a carbon and energy source for growth. The bacteria are considered anti-cariogenic as they metabolize lactic acid into propionic acid which increases oral environment’s pH and reduces demineralization rate of tooth structure. Identification of Veillonella spp. using traditional methods is difficult due to the lack of conventional phenotypic and biochemical tests. Thus, the biomolecular methods are suitable for the specific detection and identification of Veillonella spp. One of the biomolecular methods that can be used is real-time Polymerase Chain Reaction (PCR), which the results can be qualitative and quantitative. This study aimed to identify Veillonella spp. in tongue plaque’s and saliva’s samples using Real -time PCR. The DNA of Veillonella spp. derived from 36 samples, 18 samples of tongue plaque and 18 samples of saliva, were extracted using a freeze-thaw method and then quantified by real-time PCR using forward primer 5’-CCG TGA TGG GAT GGA AAC TGC-3’ and reverse primer 5’-CCT TCG CCA CTG GTG TTC TTC-3’. Veillonella spp. in 18 samples of tongue plaque was 3,06 x 107 CFU/ml and in 18 saliva samples was 1,51 x 105 CFU/ml.  It was concluded real-time PCR can detect Veillonella spp. from all tongue plaque’s and saliva’s samples.